Magnesium sulphate for prevention of eclampsia: are intramuscular and intravenous regimens equivalent? A population pharmacokinetic study. Issue 7 (26th March 2013) - Salinger, DH; Mundle, S; Regi, A; Bracken, H; Winikoff, B; Vicini, P; Easterling, T
<x xml:space="preserve">Abstract</x> Objective To compare magnesium sulphate concentrations achieved by intramuscular and intravenous regimens used for the prevention of eclampsia. Setting Low‐resource obstetric hospitals in Nagpur and Vellore, India. Population Pregnant women at risk for eclampsia due to hypertensive disease. Methods A pharmacokinetic study was performed as part of a randomised trial that enrolled 300 women comparing intramuscular and intravenous maintenance regimens of magnesium dosing. Data from 258 enrolled women were analysed in the pharmacokinetic study. A single sample was drawn per woman with the expectation of using samples in a pooled data analysis. Main outcome measures Pharmacokinetic parameters of magnesium distribution and clearance. Results Magnesium clearance was estimated to be 48.1 dl/hour, volume of distribution to be 156 dl and intramuscular bioavailability to be 86.2%. The intramuscular regimen produced higher initial serum concentrations, consistent with a substantially larger loading dose. At steady state, magnesium concentrations in the intramuscular and intravenous groups were comparable. With either regimen, a substantial number of women would be expected to have serum concentrations lower than those generally held to be therapeutic. Conclusions Clinical implications were that a larger loading dose for the intravenous regimen should be considered; where feasible, individualised dosing of magnesium sulphate would reduce the variability in serum concentrations and might result in more women with clinically effective magnesium concentrations; and lower dose magnesium suphate regimens should be considered with caution.